Effect of Pictorial Health Warnings on Fear and Intensity Smoking Cessation - Lasari, Hadrianti H.D.; Pandji Winata Nurikhwan; Maulina, Dessy; Fakhriadi, Rudi; Ahsan, Abdillah; Medyna, Ikrima; Astuti, Verinda Ghea Ayu; Firani, Dewi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: World Health Organization (2020) states that the number of smokers aged 15 years and over in the world is 991 million people. The highest number of smokers in ASEAN is in Indonesia (46.16%). Riskesdas South Kalimantan (2018) states that the prevalence of smokers in South Kalimantan is 24.42%. The highest prevalence of smoking in South Kalimantan Province in 2018 with a frequency of every day was in Kotabaru Regency at 27.37%, Hulu Sungai Tengah at 22.03%, and Banjar Regency at 20.88%. Aims: Explain and analyze the effect of pictorial health warnings on cigarette packaging on fear and intensity of smoking cessation in Kotabaru, Hulu Sungai Tengah, and Banjar districts. Method: The study used a cross-sectional design. Accidental sampling was used with a sample of 164 Kotabaru districts, 112 Hulu Sungai Tengah samples, and 224 Banjar samples. The research instrument was a modified questionnaire from WHO STEPwise and previous research which were then tested for validity and reliability. Data analysis was univariate and bivariate analysis using linear regression analysis. Results: There was a relationship between pictorial health warnings on cigarette packaging with fear (p-value = 0.0001, r = 0.731) and smoking cessation intensity (p-value = 0.0001, r = 0.771). There is a positive influence between pictorial health warnings on cigarette packaging on fear by 53.4% and smoking cessation intensity by 59.4%. Conclusion: There is an influence between pictorial health warnings on cigarette packaging on fear and smoking cessation intensity in Kotabaru, Hulu Sungai Tengah, and Banjar districts.